„Duch, który przekonywa świat o grzechu” (DeV 27). Pneumatologiczna reinterpretacja profetyczno-krytycznej misji Kościoła w świecie - Gocko, Jerzy (Verbum Vitae, 2020)
The paper is aimed at highlighting the role of the Holy Spirit in the mission of the Church in the world. (1) Besides indicating the specific directions and means of this mission, the Holy Spirit is, first and foremost, its source and consequently the source of its fruitfulness. (2) In this world, however, the Holy Spirit, as the invigorating power and light, encounters resistance and opposition, first in the internal and subjective dimension through sin, and then in the objectified shape of culture and civilization, which in modern theology found its expression in the concept of “social sin” and “structures of sin”. (3) If the Church wants to recognize and realize its ministry to the world according to the mandate received from Christ, it must be constantly open to the Holy Spirit, who “convinces the world of sin, justice and judgment” (Jn 16: 8). Today, the task of convincing the world of sin is undertaken by the Church primarily on the doctrinal level. In relation to the social sphere, this role is played by the Church’s social teaching through its prophetic and critical dimension.